Variation in timed artificial insemination pregnancy rates in specific groups of suckled beef cows - Hill, Scott L.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Insemination of beef cows at a predetermined time is a management tool to reduce labor costs associated with conventional heat detection available to cattle producers. Multiple research trials have examined the timing of the administration of the individual components of the developed protocols associated with timed artificial insemination (TAI). In the current research, we examined various classifications of postpartum beef cows and analyzed their reproductive performance when submitted to TAI protocols. The 7-day CO-Synch + controlled internal drug release (CIDR) insert protocol and the 5-day CO-Synch + CIDR protocol have been shown to effectively initiate ovulation in cycling and non-cycling suckled beef cows, producing pregnancy rates at or greater than 50% in beef cows. We hypothesized that uniformly selected groups of cows based on their progesterone status at CIDR insertion, days postpartum, body condition score, and/or parity would demonstrate improved reproductive performance compared with non-grouped cows.
Keywords: Beef; Artificial insemination; Pregnancy